Incidence of Sepsis Risk Factors in Hopsital Research using Vosviewer: A Bibliometrics Study - Galuh Shafira Savitri; Kusbaryanto Kusbaryanto (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
Risk factors of sepsis have been identified in several points such as chronic health conditions, comorbid diseases (hypertension, diabetes mellitus, HIV, and CKD), old age, male, alcohol users, immunosuppression conditions due to malignancy or use of certain drugs, obesity, length of treatment in hospital, and chemotherapy. This article aims to find out the incidence of sepsis and its risk factors in hospitals, globally in various fields. This study uses literature on the Scopus database from 2011 and Scopus Analyzing Tools. VOS Viewer (version 1.6.17) is used for bibliometrics analysis. Based on visualization results, a total of 430 articles were extracted. Most research was carried out in 2017, with 63 studies. The United States published more articles, amounting to 100 studies. The fields or areas that have been researched related to the incidence of sepsis and its factors the most are medicine. The latest keyword such as length of stay, antibiotic agent, and treatment appeared in 2016. The research trend was determined to have greatly increased in 2017 before declining once more in 2018. This research should be updated in the future to get the latest knowledge on sepsis risk factors in hospitals. Abstrak: Faktor risiko terjadinya sepsis telah diidentifikasi dalam beberapa poin seperti kondisi kesehatan kronis, penyakit komorbid (hipertensi, diabetes melitus, HIV, dan CKD), usia tua, jenis kelamin laki-laki, pengguna alcohol, kondisi imunosupresi akibat keganasan atau penggunaan obat tertentu, obesitas, lama perawatan yang dijalani di rumah sakit, dan kemoterapi yang sedang dijalani. Artikel ini bertujuan untuk mengetahui bagaimana kejadian sepsis dan faktor risikonya di rumah sakit, secara global di berbagai bidang. Penelitian ini menggunakan literatur pada database Scopus dari tahun 2011 dan dianalisis dengan menggunakan Scopus Analyzing Tools. Vos Viewer (versi 1.6.17) digunakan untuk analisis bibliometrik. Berdasarkan hasil visualisasi, total 430 artikel diekstraksi. Sebagian besar penelitian dilakukan pada tahun 2017, 63 studi. Amerika Serikat menerbitkan lebih banyak artikel, 100 studi. Bidang yang paling banyak melakukan penelitian terkait kejadian sepsis dan faktor risikonya adalah kedokteran. Kata kunci terbaru seperti lama perawatan, agen antibiotik, dan hasil terapi muncul pada tahun 2016. Tren penelitian dipastikan telah meningkat pesat pada tahun 2017 sebelum menurun kembali pada tahun 2018. Penelitian ini harus diperbarui kedepannya untuk mendapatkan pengetahun terbaru terkait faktor risiko sepsis di rumah sakit.